2020
DOI: 10.4067/s0717-95022020000200328
|View full text |Cite
|
Sign up to set email alerts
|

Body Composition Characteristics Measured By Multichannel Bioimpedance In Young Female Basketball Players: Relation With Match Performance

Abstract: ZARIC, I.; DOPSAJ, M.; MARKOVIC, M.; ZARIC, M.; JAKOVLJEVIC, S. & BERIC, D. Body composition characteristics measured by multichannel bioimpedance in young female basketball players: relation with match performance. Int. J. Morphol., 38(2):328-335, 2020. SUMMARY:The aim of this research is to investigate the correlation of morphological characteristics, that is, body composition characteristics with the competitive performance of female basketball players of cadet (U16) age, in general and depending on the pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 14 publications
0
18
0
1
Order By: Relevance
“…Considering this, body size and composition have been shown to be associated with job-related physical performance of police officers (Dawes et al, 2016;Kukic et al, 2018a,b). Furthermore, studies have shown that some physical performance can be influenced by body size and composition (Kukic et al, 2018a,b;Zaric et al, 2020). This in part contributed to the recommendation by Jaric et al (2005) who proposed the standardization of performance tests based on body size.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering this, body size and composition have been shown to be associated with job-related physical performance of police officers (Dawes et al, 2016;Kukic et al, 2018a,b). Furthermore, studies have shown that some physical performance can be influenced by body size and composition (Kukic et al, 2018a,b;Zaric et al, 2020). This in part contributed to the recommendation by Jaric et al (2005) who proposed the standardization of performance tests based on body size.…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore not surprising that next to physical activity and skill, body size, body composition, and external load are well-investigated factors associated to physical abilities (i.e. strength and aerobic power) as well as to the outcome of a number of functional performance tests (Dawes et al, 2017;Kukic et al, 2018a,b;Lockie et al, 2018;Zaric et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Se observa un ligero aumento del 1 % de la masa muscular y una reducción del 1 % de la masa grasa, datos estos no significativos. La masa muscular esquelética está muy vinculada al rendimiento en la competición (Zaric et al, 2020) Grazioli et al (2020 analizan el componente graso acumulado por el desentrenamiento en jugadores de fútbol profesionales durante el periodo de confinamiento por COVID-19 y lo comparan con el periodo de temporada baja de actividad física. Concluyen que hubo un aumento mayor y significativo de la masa grasa y peso corporal tras el periodo de confinamiento frente a una pre-temporada.…”
Section: Discussionunclassified
“…Body composition is a general indicator of the human organism condition because it is influenced by the effects of numerous factors, such as diet, health condition, level of physical activity, stress, and others (Chumlea et al, 2002;Garthe et al). However, modern elite sport, there is a need to develop sport-specific, and even more, individual and playing positions sports-specific standards as the options for the future, whether it is a standard of body composition, some physical ability, or a level of the technical and tactical aspects of performance (Nikolaidis et al;Dopsaj et al, 2017;Báez-San-Martín et al;D'Anastasio et al, 2019;Zaric et al).…”
Section: Discussionmentioning
confidence: 99%
“…However, the training type also dominantly depends on the type of sport. Today, in the sports science area, there are significant established findings regarding the relationship between physical abilities and specific motor characteristics with morphological type and body composition characteristics (Garthe et al, 2011;Ackland et al, 2012;Giannopoulos et al;Saraykin et al, 2018;Zaric et al, 2020).…”
Section: Introductionmentioning
confidence: 99%